Impact of Rainforest Conversion on Surface Runoff and Soil Erosion in Nopu Upper Catchment of Central Sulawesi - Yayat Hidayat; Naik Sinukaban; Hidayat Pawitan; Suria Darma Tarigan (UNIVERSITY OF LAMPUNG, 2008)
Rainforest conversion into agricultural lands in Nopu Upper Catchment such as cocoa plantations, maizes, cassava, peanuts, and scrub and bush were significantly increase soil erosions and surface runoffs, which in turn will decrease crops productivity and hydrologic functions of watershed. Soil erosion from maize and peanut rotation plots are higher 2.061,8% than soil erosions from natural forest plots. Soil erosions are higher also in intercroping young age cocoa, maize and cassava plots and maize plots respectively 2.023,8% and 2.012,3%. Where as surface runoffs were increase up to 650,9% in medium age cocoa plots, 380,4% in intercroping young age cacao and cassava plots, and 347,1% in scrub and bush plots. The result of ANSWERS model simulation using daily C factors were indicate that rainforest conversion into agricultural lands in Nopu Upper Catchment causing soil and water loss respectively 3.190,5 ton/year and 115.441 m3/year. Application of agroforestry systems in agricultural lands which in line with reforestation in stream line area of Nopu river and steepy agricultural lands (slope > 40%) are effectively reduce soil erosions up to 77,6% compare to soil erosion from existing land uses.